A Mekanisme Ventilasi Pasif pada Arsitektur Vernakuler: Analisis Konstruksi Timpa Laja pada Rumah Bugis Pagata - Hariadi, Akhmad; Rahman, Akbar; Febrita, Yuswinda (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
Vernacular architecture possesses climate adaptation strategies that are frequently overlooked in contemporary design. This study aims to elucidate the passive cooling mechanism of the Timpa Laja (gable roof element) in the Bugis Pagatan house. The research employs a Single Case Study method with a descriptive-analytical approach. The object of study is focused on the stilt house typology featuring a multi-tiered (two-tiered) Timpa Laja construction, representing the social stratum of community leaders. The analysis involves dissecting the timber shingle construction details and simulating airflow logic using the Stack Effect principle. The results indicate that the Timpa Laja is not merely an aesthetic status marker but functions technically as a